2019
DOI: 10.1097/mpa.0000000000001298
|View full text |Cite
|
Sign up to set email alerts
|

Recent Insights Into the Pathogenic Mechanism of Pancreatitis

Abstract: Acute pancreatitis (AP) is a potentially lethal inflammatory disease that lacks specific therapy. Damaged pancreatic acinar cells are believed the site of AP initiation. The primary function of these cells is the synthesis, storage, and export of digestive enzymes. Beginning in the endoplasmic reticulum and ending with secretion of proteins stored in zymogen granules, distinct pancreatic organelles use ATP produced by mitochondria to move and modify nascent proteins through sequential vesicular compartments. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 137 publications
(260 reference statements)
2
61
0
1
Order By: Relevance
“…A prospective analysis of 145 886 participants found that, among smokers, pancreatitis was highest among those who consumed more than four drinks a day (hazard ratio 2.06, 95% confidence interval 1.28 to 3.30) 11. Understanding of the mechanisms of pancreatitis and the roles of alcohol and smoking has increased and is covered in recent reviews 320…”
Section: Trends In Causes Of Pancreatitismentioning
confidence: 99%
“…A prospective analysis of 145 886 participants found that, among smokers, pancreatitis was highest among those who consumed more than four drinks a day (hazard ratio 2.06, 95% confidence interval 1.28 to 3.30) 11. Understanding of the mechanisms of pancreatitis and the roles of alcohol and smoking has increased and is covered in recent reviews 320…”
Section: Trends In Causes Of Pancreatitismentioning
confidence: 99%
“…The precise mechanisms of initiation and progression of CP are unclear. CP is considered to result from unresolved, recurrent fibroinflammation and is characterized by extensive loss of the normal exocrine parenchyma, widespread fibrosis and inflammation, and impairment of both exocrine and endocrine pancreatic functions (Majumder and Chari, 2016; Yang and Forsmark, 2017; Gukovskaya et al, 2019). Accumulating evidence supports the concept that pancreatitis is initiated in the pancreatic acinar cell, the main cell type in the exocrine parenchyma, with stresses causing cellular dysfunction that triggers activation of pro-inflammatory signaling, activation of neighboring quiescent pancreatic stellate cells (PaSC), and immune cell infiltration into the pancreas (Gukovskaya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrated that SPINK1 could inhibit intra-acinar trypsin activation via amelioration of impaired autophagy in cellular model of in vitro acute pancreatitis, a well-accepted AR42J-related AP setting nowadays. Since the past decade, researchers have noticed that impaired autophagy was existed during the development of acute pancreatitis [14,15 ], though the mechanisms was unraveled. On the other hand, SPINK1, as an active trypsin inhibitor, has been found to be a negative regulator of autophagy in normal pancreatic acinar cell, and the slightly enhanced trypsin activity can be detected in the isolated pancreatic acinar cells of SPINK1 knockout mouse pups [2,16].…”
Section: Discussionmentioning
confidence: 99%